2017
DOI: 10.1111/add.13887
|View full text |Cite
|
Sign up to set email alerts
|

Association between smoking and alcohol‐related behaviours: a time–series analysis of population trends in England

Abstract: AimsThis paper estimates how far monthly changes in prevalence of cigarette smoking, motivation to quit and attempts to stop smoking have been associated with changes in prevalence of high‐risk drinking, and motivation and attempts to reduce alcohol consumption in England.DesignData were used from the Alcohol and Smoking Toolkit Studies between April 2014 and June 2016. These involve monthly household face‐to‐face surveys of representative samples of ~1700 adults in England.MeasurementsAutoregressive Integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 50 publications
3
35
0
Order By: Relevance
“…Smoking-related characteristics included: smoking status, time to first cigarette, consistent motivation to stop and (because it has been shown to be associated with smoking and quitting behaviour25–27) high-risk drinking. Smoking status was self-reported by all adults in response to the question: ‘Which of the following best applies to you (current smoker/stopped in the past year/stopped more than a year ago/never smoked)?’.…”
Section: Methodsmentioning
confidence: 99%
“…Smoking-related characteristics included: smoking status, time to first cigarette, consistent motivation to stop and (because it has been shown to be associated with smoking and quitting behaviour25–27) high-risk drinking. Smoking status was self-reported by all adults in response to the question: ‘Which of the following best applies to you (current smoker/stopped in the past year/stopped more than a year ago/never smoked)?’.…”
Section: Methodsmentioning
confidence: 99%
“…Binge drinking among adolescents is associated with many additional risky behaviors, such as drug abuse and unprotected sexual behavior [ 14 , 15 , 16 ]. In addition, cigarette smoking has been found to be associated with drinking alcohol; those who smoke more cigarettes are more likely to drink more alcohol [ 17 ]. Adolescents who drink alcohol have a lower chance of overcoming smoking addictions [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there were no significant associations between motivation to stop and motivation to reduce alcohol consumption or attempts to quit smoking and attempts to reduce alcohol consumption. 22 We found the combination of results surprising and suggested that the association with overall prevalence may be related to an unmeasured variable that accounted for the change in both smoking and high-risk drinking. Alternatively, the failure to find an overall association between motivation and attempts for each behaviour may be an issue of power when focussing on the global association between subsamples that represented only a fifth of the overall sample.…”
Section: Introductionmentioning
confidence: 74%
“…These findings suggest that the previously identified positive association between prevalence of smoking and prevalence of high-risk drinking is unlikely to be causal, whereby smokers attempting to quit, and those succeeding, also reduce their alcohol intake. 22 Although it remains possible that use of alcohol by smokers impacts on other key indices including longer term abstinence, the small proportion of smokers who relapse long term (ie, after a year) could not account for the size of association noted. It may instead be that overall prevalence is related to an unmeasured variable, perhaps economic factors and sociocultural events, that accounts for the change in both smoking and high-risk drinking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation